Topology for computing - Zomorodian, Afra J., 1974- (Cambridge monographs on applied and computational mathematics, 2005)
This concise, self-contained introduction to topology and Morse theory from a computational point of view shows how to solve real problems that have topological aspects using computers. Applications include computer graphics, robotics, structural biology, and chemistry.